Faktor Pengelolaan Operasi dan Pemeliharaan Irigasi Di Kabupaten Tanah Datar - Revi Arianto; Nasfryzal Carlo; Zuherna Mizwar (Jurnal Talenta Sipil, 2023)
In recent years, the Tanah Datar district government has focused more on the physical implementation of irrigation area development and has not prioritized the budget for operating and maintenance costs so that there are still many Irrigation Areas (DI) whose irrigation infrastructure is not functioning properly with a high level of network damage that requires high costs. In addition, low awareness of the provision of operational and maintenance (OP) funds, limited human resources for OP staff, and the participation of groups of farmers using water (P3A) or a combination of groups of farmers using water (GP3A) is also not optimal. In order to function optimally and can be used for a long time, the irrigation that has been built needs to be maintained and managed systemically and to develop an optimal operating and maintenance management framework. The purpose of this study was to identify the dominant factors and factors that influence the operation and maintenance of irrigation networks in Tanah Datar District, as well as to optimize the operation and maintenance of the network. This study used a quantitative method by distributing questionnaires to respondents. The results of the research conducted revealed that there were 2 factors that influenced the operation and maintenance of irrigation networks in Tanah Datar Regency, namely the condition of physical infrastructure and supporting facilities and P3A Personnel Organization and Institutions..